2014
DOI: 10.1093/jxb/eru044
|View full text |Cite
|
Sign up to set email alerts
|

An integrative analysis of the transcriptome and proteome of the pulp of a spontaneous late-ripening sweet orange mutant and its wild type improves our understanding of fruit ripening in citrus

Abstract: Summary:ABA, ethylene, sucrose, and their related genes and pathways are involved in fruit ripening of citrus, and ABA may play a central role during the ripening process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
117
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(132 citation statements)
references
References 67 publications
11
117
0
Order By: Relevance
“…Fruit ripening is a broadly used, genetic and irreversible process that contributes to a chain of physiological, biochemical and sensory changes that result in the development of soft, mature, high-quality fruits [1, 19]. RNA-Seq technology was used to reveal the key roles of metabolic pathways during the ripening of cultivated watermelon fruit and to explore the transcriptomic differences between two contrasting cultivated watermelon genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fruit ripening is a broadly used, genetic and irreversible process that contributes to a chain of physiological, biochemical and sensory changes that result in the development of soft, mature, high-quality fruits [1, 19]. RNA-Seq technology was used to reveal the key roles of metabolic pathways during the ripening of cultivated watermelon fruit and to explore the transcriptomic differences between two contrasting cultivated watermelon genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the extensively enriched pathways in COS and LSW177, some DEGs were found to be involved in carotenoid formation, plant hormone signal transduction, sugar metabolism and cell wall metabolism and might have unique functions in cultivated watermelon during fruit ripening. These metabolic pathways are also important for fruit ripening in melon [20], tomato [21] and orange [19]. These pathways have the ability to create an organized metabolic association that possibly cooperates during fruit ripening in cultivated watermelon.…”
Section: Discussionmentioning
confidence: 99%
“…Each fraction was independently separated with an 85 min gradient comprised of 5 min to 35% buffer B (0.1% formic acid in acetonitrile), followed by 5 min linear gradient to 90% B, and maintained at 90% B for 5 min at a constant flow rate of 300 nL/min. The peptides were submitted to a nanoESI source followed by tandem mass spectrometry (MS/MS) in Q-Exactive (Thermo Scientific, USA) that was coupled online to the HPLC [33]. Peptides were sprayed into the Q-Exactive MS/MS system with a spray voltage of 1.8 kV.…”
Section: Lc-ms/ms Analysis By Q-exactivementioning
confidence: 99%
“…The complete list of identified peptides was then housed in an Excel (Microsoft) database for the grouping of results into proteins and calculation of ratios and coefficient of variation. Protein identification and quantification were performed essentially as described previously [21,33]. For protein identification, the filters were set as follows: significance threshold P b 0.05 (with 95% confidence) and ion score or expected cut-off less than 0.05 (with 95% confidence).…”
Section: Protein Identification and Quantificationmentioning
confidence: 99%
“…Yang et al (2011b) have reported that citrus fruit ripening is associated with the accumulation of primary metabolites, and the levels of sugars and organic acids determine the quality and taste of citrus fruits (Tietel et al, 2011;Chen et al, 2012). Furthermore, it has been evidenced that sugars (mainly glucose and fructose) and organic acids (mainly citric acid and malic acid) are markedly changed during sweet orange ripening (Wu et al, 2014;Yu et al, 2012), and the regulatory mechanism has been investigated increasingly with omics-based approaches, such as transcriptomics (Yu et al, 2012), proteomics (Wu et al, 2014), and metabolomics (Yang et al, 2011b). Although these studies have presented massive data which enlarge the information related to citrus fruit ripening at molecular and metabolic levels, the regulatory mechanism is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%